PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA UNIT PAYMENT COLLECTION INDIHOME PT. TELKOM INDONESIA WITEL TANGERANG - Geovalevi Marza, Ghessa; Sularmi, Lili (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of motivation and work discipline on employee performance at the Indihome PT Payment Collection Unit. Telkom Indonesia Witel Tangerang, either partially or simultaneously. The research method used is a quantitative method. Based on hypothesis testing, the results of motivation on employee performance with the value of t count < t table or 1.830 < 2.001 with a significance value of 0.072 < 0.05. So it can be concluded that partially motivation has no significant effect on employee performance. The results of the work discipline hypothesis test on employee performance obtained the value of t count> t table or 12.083> 2.001 with a significance value of 0.000 <0.05. So it can be concluded that partially work discipline has a significant effect on employee performance. Based on the results of hypothesis testing, the value of F count> F table or 75.481> 3.16 with a significance of 0.000 <0.050. So it can be concluded that simultaneously motivation and work discipline together have a significant effect on employee performance.